Comparative Evaluation of Chemical Treatment on the Physical and Mechanical Properties of Areca Frond, Banana, and Flax Fibers. Issue 4 (3rd April 2022) - Shenoy Heckadka, Srinivas; Nayak, Suhas Yeshwant; Joe, Thomas; Zachariah N, Jacob; Gupta, Sonia; Kumar N V, Anil; Matuszewska, Marta
ABSTRACT: The present work aims to understand the effect of chemical treatment on the physical and mechanical characteristics of the natural fibers, namely, areca frond fibers, banana, and flax fibers. Chemical reagents viz. sodium bicarbonate, potassium permanganate, and chromium sulfate were used for surface modifications. Tensile strength of the fibers was determined for analyzing the influence of treatments. Scanning electron microscopy was adopted to visualize the surface morphology. Fourier transform infrared spectroscopy was performed on the fiber specimen to interpret functional group modifications. The research results indicated a decrease in fiber diameter with increase in density of fibers post treatments. For areca frond and flax fibers, chromium sulfate treatment was the most effective while that for banana fibers sodium bicarbonate based treatment turned out to be most effective over the others. Scanning electron microscopy images confirmed clear visibility of fiber inner cell structure, protruding secondary fibrils for treated fibers, reagent coating on the fiber surface was also observed in the case of chromium sulfate-treated samples. Fourier transform infrared spectroscopy analysis showed distinct bands indicating functional group modifications corresponding to cellulose, hemicellulose, and lignin.